Method for preparing polyethylene polymerization catalyst
By adjusting the viscosity of the first mixed solution to control the catalyst morphology, the problem of uneven catalyst size and morphology in the prior art is solved, and the uniformity and excellent morphology of the polyethylene polymerization catalyst are achieved, and the solvent usage amount and cost are reduced.
Patent Information
- Application Number
- CN202410064641.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-05
- Filing Date
- 2024-01-17
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, when preparing Ziegler-Natta catalysts, it is difficult to effectively adjust the size and morphology of the catalyst, resulting in problems of unevenness and poor morphology of polymer particles, especially in the extension process of lithium-ion battery separator resin.
The catalyst morphology is initially controlled by adjusting the viscosity of the first mixed solution before adding the internal electron donor, thereby preparing a polyethylene polymerization catalyst with uniform catalyst size and excellent catalyst morphology.
In the simplified process, uniform catalyst size and excellent catalyst morphology are achieved, the solvent usage is reduced, the cost is reduced, and the particle size uniformity and fluidity of the polymer are improved.
Smart Images

Figure CN119775460A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a polyethylene polymerization catalyst. Background Art
[0002] Polymer particles polymerized using Ziegler-Natta catalysts are usually affected by the catalyst used. Therefore, the technology of adjusting the size and morphology of the Ziegler-Natta catalyst when preparing the catalyst has a great influence on the polymer particles, and thus becomes the key to generating the desired polymer. In particular, the resin used in the preparation of lithium-ion battery separators (LiBS) needs to be subjected to an extension process after oil mixing, so the size and distribution of the resin are very important factors.
[0003] One of the existing technologies for adjusting the size and morphology of the catalyst is to dissolve the carrier in a soluble solvent and then recrystallize it. As for the recrystallization technology, magnesium compounds, which are one of the most commonly used carriers, are widely used because of their high solubility in soluble solvents such as alcohols, aldehydes, and amines.
[0004] Among them, when alcohol is used together with a hydrocarbon solvent such as decane, the magnesium compound is completely dissolved at a high temperature of 100°C or higher, so that the magnesium compound does not reprecipitate at room temperature in the form of a mixed solution. These mixed solutions can be treated by various treatment methods to prepare a solid component catalyst.
[0005] However, when alcohol is used to completely dissolve magnesium chloride at high temperature, when the temperature is lowered for recrystallization, cavitation may occur during stirring.
[0006] In order to prevent cavitation during the stirring, a solvent may be added, but the addition of a solvent increases the size of the catalyst and results in a poor catalyst morphology, so that the desired catalyst size or excellent catalyst morphology cannot be obtained. Moreover, as the amount of solvent used increases, the cost increases.
[0007] In addition, the period of adding the transition metal compound during recrystallization is an important stage in preparing catalyst seeds. The size and morphology of the catalyst will change excessively depending on the temperature and the addition time, so there is a problem of difficulty in obtaining the desired catalyst size and shape.
[0008] It is necessary to develop a technology that can solve the problems described above. Summary of the invention
[0009] Technical issues to be solved
[0010] According to one aspect of the present invention, the catalyst morphology is preliminarily controlled by adjusting the viscosity of the first mixed solution before adding the internal electron donor, so that a polyethylene polymerization catalyst having uniform catalyst size and excellent catalyst morphology can be prepared.
[0011] According to one aspect of the present invention, when preparing a polyethylene polymerization catalyst, uniform catalyst size and excellent catalyst morphology can be easily and simply obtained by controlling only the viscosity variable of the first mixed solution without controlling other various variables in the catalyst preparation method.
[0012] According to one aspect of the present invention, a method for preparing a polyethylene polymerization catalyst having excellent economic efficiency by reducing the amount of solvent used can be provided.
[0013] According to one aspect of the present invention, a polymer having uniform particle size and excellent fluidity can be prepared by controlling the active site of the catalyst.
[0014] According to one aspect of the present invention, in a method for preparing a polyethylene polymerization catalyst, the occurrence of cavitation generated during stirring can be prevented.
[0015] According to one aspect of the present invention, by easily controlling the recrystallization step of adding a transition metal compound to prepare catalyst seed crystals, a desired catalyst size and catalyst morphology can be easily obtained.
[0016] According to one aspect of the present invention, polyethylene with more uniform particle size can be obtained when preparing polyethylene.
[0017] According to one aspect of the present invention, the molecular weight of a polymer can be simply increased by utilizing an existing method for preparing a catalyst.
[0018] Technical Solution
[0019] The present invention can provide a method for preparing a polyethylene polymerization catalyst, which comprises the following steps: a step of preparing a first mixed solution, which is to mix a magnesium compound, a first hydrocarbon compound and an alcohol to prepare the first mixed solution; a viscosity adjustment step, which is to add a second hydrocarbon compound to the first mixed solution to adjust the viscosity of the first mixed solution; a step of preparing a second mixed solution, which is to add a first internal electron donor to the first mixed solution with adjusted viscosity to prepare a second mixed solution; and a recrystallization step, which is to add a transition metal compound to the second mixed solution for recrystallization.
[0020] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, the viscosity of the first mixed solution at 25° C. in the viscosity adjustment step may range from 10 to 70 cP.
[0021] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a washing step of washing with a second hydrocarbon compound may be further included after the recrystallization step.
[0022] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a step of preparing a slurry catalyst by adding a second hydrocarbon compound to prepare the slurry catalyst may be further included after the washing step.
[0023] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a second internal electron donor may be further added after adding the transition metal compound.
[0024] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a molar ratio of the magnesium compound to the second internal electron donor may be 1:0.01 to 1:1.
[0025] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a molar ratio of the magnesium compound to the second hydrocarbon compound may be 1:1.5 to 1:5.
[0026] The alcohol according to one embodiment of the present invention may be at least one selected from 2-ethylhexanol, methanol, ethanol, propanol, butanol, pentanol, cyclopentanol, hexanol, heptanol, octanol, decanol, dodecanol, 2-methylpentanol, 2-ethylbutanol, cyclohexanol, methylcyclohexanol and methylbenzyl alcohol.
[0027] In one embodiment according to the present invention, the first hydrocarbon compound may be a C9 to C30 hydrocarbon.
[0028] In one embodiment according to the present invention, the second hydrocarbon compound may be a C3 to C8 hydrocarbon.
[0029] In one embodiment according to the present invention, the first internal electron donor or the second internal electron donor can be independently selected from ethyl benzoate, methyl benzoate, ethyl p-methoxybenzoate, methyl p-ethoxybenzoate, ethyl p-ethoxybenzoate, ethyl p-chlorobenzoate, diisobutyl phthalate, 9,9-bis(methoxymethyl)fluorene, propyl benzoate, isopropyl benzoate, tert-butyl benzoate, tert-butyl 4-(2-aminoethyl)benzoate, ethyl 4-(dimethylamino)benzoate, 4-(butylamino)benzoate, tert-butyl 4-(2-aminoethyl)benzoate, tert-butyl 4-(dimethyl ...2-aminoethyl)benzoate, tert-butyl 4-(2-aminoethyl)benzoate, tert-butyl 4-(dimethylamino)benzoate, tert-butyl 4-(2-aminoethyl)benzoate, tert-butyl 4-(2-hydroxyethoxy)benzoic acid methyl ester, 4-(cyanomethyl)benzoic acid methyl ester, 4-(bromomethyl)benzoic acid methyl ester, 3-(bromomethyl)benzoic acid methyl ester, 1,2-dimethoxybenzene, 1,2-diethoxybenzene, 1,2-dibutoxybenzene, 1,2-di-sec-butoxybenzene, 1,2-di-tert-butyl Oxybenzene, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane, n-propyltriethoxysilane, decyltrimethoxysilane, cyclopentyltrimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethylcyclopentyltrimethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane, tert-butyltriethoxysilane, n-butyltriethoxysilane, isobutyltriethoxysilane, At least one of decyltriethoxysilane, cyclopentyltriethoxysilane, cyclohexyltriethoxysilane, chlorotriethoxysilane, ethyltriisopropoxysilane, vinyltributoxysilane, trimethylphenoxysilane, methyltriallyloxysilane, vinyltriacetoxysilane, dimethylmethoxysilane, diisopropyldimethoxysilane, tert-butylmethyldimethoxysilane, dicyclopentyldimethoxysilane, dicyclohexyldimethoxysilane, cyclohexylmethyldimethoxysilane, diphenyldimethoxysilane and cyclopentyldimethoxysilane.
[0030] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a molar ratio of the magnesium compound to the first internal electron donor may be 1:0.01 to 1:0.3.
[0031] In the method for preparing the polyethylene polymerization catalyst according to one embodiment of the present invention, a molar ratio of the magnesium compound to the transition metal compound may be 1:2 to 1:5.
[0032] In one embodiment according to the present invention, the recrystallization step may be performed at -7°C to 7°C.
[0033] Furthermore, the present invention may provide a method for preparing polyethylene, comprising the step of polymerizing monomers using the polyethylene polymerization catalyst prepared according to the method for preparing the polyethylene polymerization catalyst.
[0034] Beneficial Effects
[0035] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, the catalyst morphology is preliminarily controlled by adjusting the viscosity of the first mixed solution before adding the internal electron donor, so that a polyethylene polymerization catalyst having uniform catalyst size and excellent catalyst morphology can be prepared.
[0036] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, when preparing a polyethylene polymerization catalyst, a catalyst showing uniform catalyst size and excellent catalyst morphology can be easily and simply obtained by only controlling the viscosity variable of the first mixed solution without controlling various other variables in the catalyst preparation method.
[0037] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, a method for preparing a polyethylene polymerization catalyst having excellent economic efficiency by reducing the amount of solvent used can be provided.
[0038] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, a polymer having uniform particle size and excellent fluidity can be prepared by controlling the active sites of the catalyst.
[0039] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, the occurrence of cavitation generated during stirring can be prevented.
[0040] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, the desired catalyst size and catalyst morphology can be easily obtained by easily controlling the recrystallization step of adding a transition metal compound to prepare catalyst seed crystals.
[0041] When polyethylene is prepared using the polyethylene polymerization catalyst prepared by the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, polyethylene having a more uniform particle size can be obtained.
[0042] When polyethylene is prepared using the polyethylene polymerization catalyst prepared by the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, the molecular weight of the polymer can be simply increased by using the existing method for preparing the catalyst.
[0043] The catalyst prepared by the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention can be used for the production of eco-friendly polymers. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a scanning electron microscope (SEM) image showing the catalyst prepared according to Example 1 of the present invention.
[0045] Figure 2 is a scanning electron microscope (SEM) image showing the catalyst prepared according to Example 2 of the present invention.
[0046] Figure 3 is a scanning electron microscope (SEM) image showing the catalyst prepared according to Example 3 of the present invention.
[0047] Figure 4 is a scanning electron microscope (SEM) image showing the catalyst prepared in Comparative Example 1 according to the present invention.
[0048] Figure 5 is a scanning electron microscope (SEM) image showing the catalyst prepared in Comparative Example 2 according to the present invention.
[0049] Figure 6 is a scanning electron microscope (SEM) image showing the catalyst prepared in Comparative Example 3 according to the present invention.
[0050] Figure 7 is a scanning electron microscope (SEM) image showing the catalyst prepared in Comparative Example 4 according to the present invention.
[0051] Figure 8 is a graph showing polymer particle size distribution of slurry catalyst and dried catalyst according to one embodiment of the present invention. DETAILED DESCRIPTION
[0052] By referring to the embodiments described in detail below, the advantages and features of the present invention and the methods for achieving them can be clearly understood. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various ways different from each other. This embodiment is only provided for the purpose of fully disclosing the present invention and fully explaining the scope of the present invention to those skilled in the art to which the present invention belongs. The present invention is only defined by the scope of the claims.
[0053] Unless otherwise defined, all terms (including technical terms and scientific terms) used in the specification may be used as meanings that may be commonly understood by those skilled in the art to which the present invention belongs.
[0054] Unless otherwise specifically stated, the singular forms of the terms used in this specification may be construed as also including the plural forms.
[0055] The numerical range used in this specification includes the lower limit and the upper limit and all values in the range, the increments logically derived in the form and width of the defined range, all values defined therein, and all possible combinations of the upper and lower limits of the numerical range defined in different forms. Unless otherwise specifically defined, the values outside the numerical range that may be generated in the specification of the present invention due to experimental errors or rounding of values are also included in the defined numerical range.
[0056] The words “include / comprise” mentioned in this specification are open-ended statements that have equivalent meanings to expressions such as “have”, “contain”, “have”, and “characterized by”, and do not exclude elements, materials or processes that are not further listed.
[0057] Unless otherwise defined, the unit of % used in the present specification means weight % unless otherwise specified.
[0058] Unless otherwise specifically defined, “A to B” in the present specification means “A or more and B or less”.
[0059] The term "C A -C B " means "the number of carbon atoms is greater than A and less than B".
[0060] Hereinafter, the method for preparing a polyethylene polymerization catalyst and the method for preparing polyethylene of the present invention are described in detail. However, this is merely exemplary, and the present invention is not limited to the specific embodiments described exemplarily.
[0061] The present invention can provide a method for preparing a polyethylene polymerization catalyst, which comprises the following steps: a step of preparing a first mixed solution, which is to mix a magnesium compound, a first hydrocarbon compound and an alcohol to prepare the first mixed solution; a viscosity adjustment step, which is to add a second hydrocarbon compound to the first mixed solution to adjust the viscosity of the first mixed solution; a step of preparing a second mixed solution, which is to add a first internal electron donor to the first mixed solution with adjusted viscosity to prepare a second mixed solution; and a recrystallization step, which is to add a transition metal compound to the second mixed solution for recrystallization.
[0062] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, the catalyst morphology is preliminarily controlled by adjusting the viscosity of the first mixed solution before adding the internal electron donor, so that a polyethylene polymerization catalyst having uniform catalyst size and excellent catalyst morphology can be prepared.
[0063] In addition, in the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, when preparing a polyethylene polymerization catalyst, a catalyst showing uniform catalyst size and excellent catalyst morphology can be easily and simply obtained by only controlling the viscosity variable of the first mixed solution without controlling various other variables in the catalyst preparation method.
[0064] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, before adding the internal electron donor, the catalyst morphology is preliminarily controlled by adding the second hydrocarbon compound to the first mixed solution in the viscosity adjustment step. When the internal electron donor is added to the first mixed solution whose viscosity is adjusted, the dispersibility of the internal electron donor in the first mixed solution increases, thereby making it easy to control the active sites, and a catalyst showing excellent catalyst morphology can be obtained.
[0065] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, a method for preparing a polyethylene polymerization catalyst with excellent economic efficiency by reducing the amount of solvent used can be provided. In the method for preparing the polyethylene polymerization catalyst, when the amount of solvent used, such as a hydrocarbon compound, increases, the economic efficiency of the process deteriorates. In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, by reducing the amount of solvent used while obtaining excellent catalyst morphology, a method for preparing a catalyst with excellent economic efficiency can be provided.
[0066] In addition, in the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, the catalyst morphology is preliminarily controlled by controlling the viscosity of the first mixed solution before adding the internal electron donor, thereby controlling the active site of the catalyst, and a polymer with uniform particle size and excellent fluidity can be prepared.
[0067] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, by controlling the viscosity of the first mixed solution before adding the internal electron donor, cavitation is prevented from occurring during stirring, thereby obtaining a catalyst showing excellent catalyst morphology and uniform catalyst size.
[0068] In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, by easily controlling the recrystallization step of adding a transition metal compound to prepare catalyst seed crystals, the desired catalyst size and catalyst morphology can be easily obtained. Generally, the size and morphology of the catalyst in the recrystallization step will vary too much depending on the temperature or the addition time of the transition metal compound, so there is a problem of difficulty in obtaining the desired size and morphology of the catalyst. In the method for preparing a polyethylene polymerization catalyst according to one embodiment of the present invention, after preparing a first mixed solution, the catalyst morphology is preliminarily controlled by adjusting the viscosity of the first mixed solution in the viscosity adjustment step, and then the recrystallization step is performed, so there is an effect of easily obtaining a catalyst showing the desired catalyst size and morphology.
[0069] According to one embodiment of the present invention, in the method for preparing the polyethylene polymerization catalyst, the viscosity range of the first mixed solution at 25°C in the viscosity adjustment step can be above 10cP, above 11cP, above 13cP, above 15cP, above 20cP, above 25cP, above 30cP, above 40cP, above 50cP, above 60cP, above 65cP, below 70cP, below 60cP, below 50cP, below 40cP, below 30cP, below 25cP, below 20cP, below 15cP, below 13cP, below 11cP or values between the values, specifically 10-70cP, 10-30cP, 20-70cP or 15-30cP, but is not limited thereto.
[0070] When the viscosity of the first mixed solution at 25° C. in the viscosity adjustment step exceeds 70 cP, the catalyst morphology is poor and the catalyst size is non-uniform. This can be Figure 4 It was confirmed that this was because when the viscosity of the first mixed solution at 25° C. exceeded 70 cP, cavitation occurred during stirring, resulting in the inability to well control the morphology and size of the catalyst.
[0071] In addition, when the viscosity of the first mixed solution at 25° C. in the viscosity adjustment step is less than 10 cP, it is confirmed that the catalyst has an uneven and poor morphology. Figure 5 It was confirmed that this is because when the viscosity of the first mixed solution at 25° C. is less than 10 cP, the viscosity of the first mixed solution is too low, resulting in a decrease in stirring efficiency.
[0072] Furthermore, when the second hydrocarbon is added in the viscosity adjustment step, the viscosity of the first mixed solution at 25° C. needs to be adjusted to above 10 cP, thereby preventing excessive addition of the second hydrocarbon and improving process economy when preparing the catalyst.
[0073] In the present invention, the magnesium compound is non-reducible, for example, the magnesium compound may be a magnesium halide such as magnesium chloride, magnesium bromide, magnesium fluoride, magnesium iodide, etc.; an alkoxy magnesium halide such as methoxy magnesium chloride, ethoxy magnesium chloride, isopropoxy magnesium chloride, butoxy magnesium chloride, octyloxy magnesium chloride, etc.; an aryloxy magnesium halide such as phenoxy magnesium chloride; an alkoxy magnesium such as ethoxy magnesium, isopropoxy magnesium, butoxy magnesium, etc. These magnesium compounds may be used in combination of two or more, but are not limited thereto. Specifically, the magnesium compound may be a magnesium halide, more specifically magnesium chloride.
[0074] According to one embodiment of the present invention, the alcohol can be selected from at least one of 2-ethylhexanol, methanol, ethanol, propanol, butanol, amyl alcohol, cyclopentanol, hexanol, heptanol, octanol, decanol, dodecanol, 2-methylpentanol, 2-ethylbutanol, cyclohexanol, methylcyclohexanol and methylbenzyl alcohol, but is not limited thereto. Specifically, the alcohol can be 2-ethylhexanol. In the present invention, the alcohol is combined with the magnesium compound to form pores and has an impact on the catalyst performance.
[0075] According to one embodiment of the present invention, the first mixed solution can be formed by simply mixing and / or stirring the magnesium compound, the first hydrocarbon compound and the alcohol, but heating can greatly facilitate the dissolution of the magnesium compound. The dissolution temperature can be 100-150°C.
[0076] In the present invention, the molar ratio of the magnesium compound to the alcohol may be 1:0.5 to 1:10, specifically 1:1 to 1:5. For the dissolution of the magnesium compound, generally, the higher the molar ratio of the alcohol or the higher the dissolution temperature, the easier it is to dissolve.
[0077] The method for preparing the polyethylene polymerization catalyst of the present invention may further include a washing step of washing with a second hydrocarbon compound after the recrystallization step.
[0078] The method for preparing the polyethylene polymerization catalyst of the present invention may further include, after the washing step, a step of preparing a slurry catalyst by adding a second hydrocarbon compound.
[0079] When polyethylene is prepared using the slurry catalyst prepared by the method for preparing the polyethylene polymerization catalyst, Figure 8 It can be confirmed that polyethylene having a more uniform particle size can be obtained.
[0080] The method for preparing the polyethylene polymerization catalyst of the present invention may further add a second internal electron donor after adding the transition metal compound.
[0081] In the method for preparing a polyethylene polymerization catalyst of the present invention, by further adding a second internal electron donor after adding a transition metal compound, the active sites of the catalyst can be made uniform without changing the existing catalyst preparation method, thereby simply increasing the molecular weight of the polymer. This means that even without changing the existing catalyst preparation formula, the molecular weight of the polymer can be simply adjusted by further adding a second internal electron donor.
[0082] According to one embodiment of the present invention, the first hydrocarbon compound may be a C9 to C30 hydrocarbon, but is not limited thereto. For example, the first hydrocarbon compound may be at least one selected from decane, benzene, toluene, xylene, ethylbenzene, dodecane, tetradecane, cyclohexane, cyclooctane, methylcyclopentane and methylcyclohexane. Specifically, the first hydrocarbon compound may be decane. The first hydrocarbon compound disperses the magnesium compound in the first mixed solution.
[0083] The molar ratio of the magnesium compound to the first hydrocarbon compound of the present invention may be 1:0.1 to 1:10, specifically 1:1 to 1:5, but is not limited thereto.
[0084] In the present invention, the second hydrocarbon compound may be a C3 to C8 hydrocarbon. For example, the second hydrocarbon compound may be at least one selected from propane, butane, pentane, hexane, heptane and octane. Specifically, the second hydrocarbon compound may be hexane.
[0085] The molar ratio of the magnesium compound to the second hydrocarbon compound of the present invention may be 1:1.5 to 1:5, specifically 1:2 to 1:5, more specifically 1:4 to 1:5, and furthermore, 1:2.5 to 1:4.
[0086] The higher the molar ratio of the second hydrocarbon compound to the magnesium compound, the greater the catalyst particle size. This is because the higher the molar ratio of the second hydrocarbon compound, the greater the impact on the recrystallization rate or stirring efficiency of the recrystallization step. The method for preparing a polyethylene polymerization catalyst of the present invention can easily adjust the catalyst particle size by adjusting the molar ratio of the second hydrocarbon compound to the magnesium compound.
[0087] According to one embodiment of the present invention, the first internal electron donor or the second internal electron donor can be independently ethyl benzoate, methyl benzoate, ethyl p-methoxybenzoate, methyl p-ethoxybenzoate, ethyl p-ethoxybenzoate, ethyl p-chlorobenzoate, diisobutyl phthalate, 9,9-bis(methoxymethyl)fluorene, propyl benzoate, isopropyl benzoate, tert-butyl benzoate, tert-butyl 4-(2-aminoethyl)benzoate, ethyl 4-(dimethylamino)benzoate, 4-(butylamino)benzoate, Ethyl formate, ethyl 4-(bromomethyl)benzoate, ethyl 4-(benzyloxy)benzoate, methyl 4-(hydroxymethyl)benzoate, methyl 4-(aminomethyl)benzoate, methyl 3-(carbamoyl)benzoate, methyl 4-(2-hydroxyethoxy)benzoate, methyl 4-(cyanomethyl)benzoate, methyl 4-(bromomethyl)benzoate, methyl 3-(bromomethyl)benzoate, 1,2-dimethoxybenzene, 1,2-diethoxybenzene, 1,2-dibutoxybenzene, 1,2-di-sec-butoxybenzene, 1,2-di-tert-butoxy Benzene, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane, n-propyltriethoxysilane, decyltrimethoxysilane, cyclopentyltrimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethylcyclopentyltrimethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane, tert-butyltriethoxysilane, n-butyltriethoxysilane, isobutyltriethoxysilane, decyltrimethoxysilane, cyclopentyltrimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethylcyclopentyltrimethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane, tert-butyltriethoxysilane, n-butyltriethoxysilane, isobutyltriethoxysilane, At least one of triethoxysilane, cyclopentyltriethoxysilane, cyclohexyltriethoxysilane, chlorotriethoxysilane, ethyltriisopropoxysilane, vinyltributoxysilane, trimethylphenoxysilane, methyltriallyloxysilane, vinyltriacetoxysilane, dimethylmethoxysilane, diisopropyldimethoxysilane, tert-butylmethyldimethoxysilane, dicyclopentyldimethoxysilane, dicyclohexyldimethoxysilane, cyclohexylmethyldimethoxysilane, diphenyldimethoxysilane and cyclopentyldimethoxysilane. Specifically, the first internal electron donor or the second internal electron donor can be ethyl benzoate or methyl benzoate, respectively, but is not limited thereto. The internal electron donor stabilizes the active site of the transition metal compound by supplying electrons to the transition metal compound.
[0088] In the present invention, the molar ratio of the magnesium compound to the first internal electron donor may be 1:0.01 to 1:0.3, specifically 1:0.05 to 1:0.20, but is not limited thereto.
[0089] The molar ratio of the magnesium compound to the second internal electron donor of the present invention may be 1:0.001 to 1:1, specifically 1:0.01 to 1:0.2.
[0090] In the present invention, the transition metal compound can be titanium tetrahalide such as TiCl4, TiBr4, TiI4; alkoxy titanium trihalide such as Ti(OCH3)Cl3, Ti(OC2H5)Cl3, Ti(OC2H5)Br3; alkoxy titanium dihalide such as Ti(OCH3)2Cl2, Ti(OC2H5)2Cl2, Ti(OC2H5)2Br2; or alkoxy titanium trihalide such as Ti(O CH3)3Cl, Ti(OC2H5)3Cl, Ti(OC2H5)3Br, etc., and can specifically be TiCl4 (titanium tetrachloride), but is not limited thereto.
[0091] In the present invention, the molar ratio of the magnesium compound to the transition metal compound may be 1:1 to 1:7, specifically 1:2 to 1:5. When the molar ratio of the transition metal compound to the magnesium compound exceeds 1:7, the proportion of the transition metal compound remaining in the polymer becomes high, which may cause problems related to environmental pollution.
[0092] In the present invention, the recrystallization step can be performed at -7°C to 7°C, specifically -5°C to 5°C.
[0093] When the recrystallization step is performed at a temperature exceeding 7°C, a bulky catalyst morphology appears and the catalyst size is not uniform. This can be Figure 6 It was confirmed that this was because the temperature of the recrystallization step was high, and the temperature was not controlled when the reaction heat was generated, so the recrystallization proceeded rapidly, resulting in the growth rate of the catalyst particles being too fast and uniform recrystallization being unable to be achieved.
[0094] Even when the recrystallization step is carried out at a temperature below -7°C, an inhomogeneous and poor catalyst morphology is confirmed. Figure 7 It was confirmed that this was because as the temperature decreased, the viscosity of the mixed solution increased, resulting in a decrease in stirring efficiency, and the concentration difference caused by bubbles generated by cavitation during stirring led to uneven recrystallization.
[0095] In the present invention, the dropwise addition time of the transition metal compound may be 0.5-4 hours, specifically 1-2 hours.
[0096] In the present invention, the recrystallization step can be carried out under stirring at a stirring speed of 50-2000rpm, specifically 100-700rpm, and more specifically 100-500rpm. When the stirring speed is too slow, the catalyst particles aggregate, making it difficult to obtain an excellent and uniform catalyst morphology. On the other hand, when the stirring speed is faster, the stirring efficiency increases, thereby improving the catalyst morphology, and the catalyst particle size tends to decrease.
[0097] The method for preparing a polyethylene polymerization catalyst according to the present invention may further include a heating step after the recrystallization step. The heating may be performed at 0.1-2°C / minute, and specifically may be performed at 0.2-1°C / minute. In addition, the heating may also be performed twice at different heating rates. For example, the temperature may be increased to 20°C at a rate of 0.5°C / minute and then increased to 80°C at a rate of 1.0°C / minute. The heating may be performed to 70-90°C. When the temperature is increased at a faster rate than the above-mentioned heating rate, the catalyst may break or aggregate, which may have a negative impact on the catalyst morphology. Afterwards, the temperature may be maintained for 2-4 hours for the stabilization of the catalyst.
[0098] The method for preparing a polyethylene polymerization catalyst according to the present invention may further include a step of reacting the catalyst prepared through the recrystallization step with an alkyl aluminum compound.
[0099] Furthermore, the present invention may provide a method for preparing polyethylene, the method comprising the step of polymerizing monomers using the polyethylene polymerization catalyst prepared according to the method for preparing the polyethylene polymerization catalyst.
[0100] The contents described with respect to the method for preparing a polyethylene polymerization catalyst are also applicable to the description of the method for preparing polyethylene within the scope of repetition.
[0101] The method for preparing polyethylene according to the present invention can prepare a polymer having uniform particle size and excellent fluidity by controlling the active sites of a polyethylene polymerization catalyst.
[0102] The method for preparing polyethylene according to one embodiment of the present invention can obtain polyethylene with more uniform particle size when preparing polyethylene by using a slurry catalyst prepared by the method for preparing the polyethylene polymerization catalyst.
[0103] In the method for preparing polyethylene according to one embodiment of the present invention, when polyethylene is prepared using a polyethylene polymerization catalyst prepared according to the method for preparing a polyethylene polymerization catalyst, the molecular weight of the polymer can be simply increased by further adding an internal electron donor while utilizing the existing method for preparing the catalyst.
[0104] The embodiments of the present invention are further described below with reference to specific experimental examples. The examples and comparative examples included in the experimental examples are only used to illustrate the present invention and are not used to limit the claims. Various variations and modifications can be made to the examples within the scope of the scope and technical concept of the present invention, which is obvious to those skilled in the art, and it is natural that such variations and modifications belong to the scope of the claims.
[0105] Evaluation example
[0106] [Measurement method]
[0107] The morphology of the catalysts and the morphology of polyethylene prepared according to the following examples and comparative examples were observed by electron microscopy (scanning electron microscope SEM, SU8230, Hitachi) and are shown in Figures 1 to 7 middle.
[0108] The distribution and particle size of the catalyst and polymer were measured by a laser particle size analyzer (Mastersizer 3000; manufactured by Malvern Instruments) by light transmission method. The cumulative distribution graph of the particle size was obtained, and the average particle diameter and particle size distribution index of the particles were calculated as follows and recorded in Table 1.
[0109] Average particle size (D50): particle size corresponding to 50% of the cumulative weight
[0110] Particle size distribution index (SPAN): P = (D90-D10) / D50
[0111] (The D90 is the particle size corresponding to 90% of the cumulative weight, and the D10 is the particle size corresponding to 10% of the cumulative weight.)
[0112] The molecular weight of the polymer was calculated by analyzing the intrinsic viscosity (η) value using an intrinsic viscosity (η) measuring device Crystex 42 (manufactured by Polymer Char) and then applying it to the Mark-Houwink Equation to obtain the molecular weight.
[0113] Mark-Houwink equation, Mv = 5.37 × 10 4 [η] 1.49
[0114] [Example 1]
[0115] Catalyst preparation
[0116] 5g of magnesium chloride, 24.7mL of 2-ethylhexanol and 25mL of decane were added to a stirrable 500mL reactor and stirred at 300rpm at 50°C to prepare a first mixed solution. The first mixed solution was heated to 135°C and kept for 2 hours. The temperature was then lowered to 60°C and 20mL of hexane was added for 30 minutes. The temperature was lowered to 25°C and 0.55mL of ethyl benzoate was added to the first mixed solution in which the viscosity was adjusted to 20.34cP by adding the hexane and kept for 30 minutes. The temperature was then lowered to 2°C, stirred at 500rpm, and 18.43ml of titanium tetrachloride was slowly added. After the addition was completed, it was kept for 30 minutes and then heated to 20°C at a rate of 0.5°C / min. It was then heated to 80°C at a rate of 1.0°C / min and kept for 120 minutes. Thereafter, stirring was stopped, the temperature was lowered to 60° C., and the mixture was washed twice with 120 mL of hexane. The temperature was lowered to 40° C., and the mixture was washed three times with 120 mL of hexane and then dried to obtain a catalyst.
[0117] Preparation of polyethylene
[0118] Under nitrogen atmosphere, 1.5L of hexane was added to a 3L reactor. Then, 1.0mmol of diluted triethylaluminum was added to the hexane, and then 5mg of the catalyst was added. The reactor temperature was raised to 80°C while stirring at 500rpm. After that, 5.0 bar of ethylene was supplied to maintain the pressure. The polymerization was continued for 90 minutes, and ethylene was supplied to keep the pressure constant. After the reaction was terminated, the reduced pressure was filtered to remove the solvent and dried in a vacuum oven to obtain polyethylene.
[0119] [Example 2]
[0120] The same method as in Example 1 was performed except that 10 mL of hexane was added and the viscosity of the first mixed solution was adjusted to 44.65 cP at 25°C.
[0121] [Example 3]
[0122] The same method as in Example 1 was performed except that 30 mL of hexane was added and the viscosity of the first mixed solution was adjusted to 11.68 cP at 25°C.
[0123] [Comparative Example 1]
[0124] The same method as in Example 1 was carried out except that hexane was not added and the viscosity of the first mixed solution was not adjusted.
[0125] [Comparative Example 2]
[0126] The same method as in Example 1 was performed except that 40 mL of hexane was added and the viscosity of the first mixed solution was adjusted to 9.17 cP at 25°C.
[0127] [Comparative Example 3]
[0128] The same method as in Example 1 was carried out except that the temperature in the recrystallization step was 10°C instead of 2°C.
[0129] [Comparative Example 4]
[0130] The same method as in Example 1 was carried out except that the temperature in the recrystallization step was -10°C instead of 2°C.
[0131] The average particle size and particle size distribution index SPAN of the catalysts prepared according to the examples and comparative examples were measured, and the morphology of the catalysts was confirmed, which is recorded in Table 1 below.
[0132] [Table 1]
[0133]
[0134] It can be confirmed that the catalyst prepared according to Example 3 shows an excellent catalyst morphology that is uniform and close to spherical.
[0135] Compared with the catalyst prepared according to Example 3, it was confirmed that the catalyst prepared according to Example 2 showed more uniform and excellent catalyst morphology.
[0136] Compared with the catalysts prepared according to Examples 3 and 2, it was confirmed that the catalyst prepared according to Example 1 not only showed the most uniform and excellent catalyst morphology, but also had significantly reduced fine powder.
[0137] It can be confirmed that the catalyst morphology of the catalyst prepared by the method of preparing the catalyst according to Comparative Examples 1 and 2 in which the viscosity of the first mixed solution at 25°C exceeds the range of 10-70 cP or Comparative Examples 3 and 4 in which the recrystallization temperature exceeds the range of -7°C to 7°C is not close to spherical and is uneven.
[0138] [Example 4]
[0139] Preparation of slurry catalyst
[0140] The same method as in Example 1 was performed except that 100 mL of hexane was added to prepare a slurry catalyst without drying after washing with hexane when preparing the catalyst.
[0141] Compared with the catalyst prepared according to Example 1, Figure 8 It can be confirmed that when polyethylene is prepared using the slurry catalyst prepared in Example 4, polyethylene having a more uniform particle size can be obtained.
[0142] [Example 5]
[0143] The same method as in Example 1 was used except that 0.75 mL of ethyl benzoate was further added during the temperature increase after titanium tetrachloride was added during the preparation of the catalyst.
[0144] The molecular weight and particle size distribution of the obtained polyethylene were measured and are shown in Table 2 below.
[0145] [Table 2]
[0146]
[0147] As can be confirmed in Example 5, in the method for preparing a catalyst of the present invention, when ethyl benzoate is further added after adding titanium tetrachloride, the molecular weight of the polymer can be simply increased by simply adding ethyl benzoate after adding titanium tetrachloride without changing the previous method for preparing a catalyst.
[0148] The above contents are merely examples of the principles of the present invention, and other configurations may be further included without departing from the scope of the present invention.
Claims
1. A method for preparing a polyethylene polymerization catalyst, comprising the following steps: a step of preparing a first mixed solution, which comprises mixing a magnesium compound, a first hydrocarbon compound and an alcohol to prepare the first mixed solution; a viscosity adjustment step, which comprises adding a second hydrocarbon compound to the first mixed solution to adjust the viscosity of the first mixed solution; a step of preparing a second mixed solution, which comprises adding a first internal electron donor to the first mixed solution with adjusted viscosity to prepare the second mixed solution; as well as The recrystallization step is to add a transition metal compound to the second mixed solution to perform recrystallization.
2. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The viscosity of the first mixed solution at 25° C. in the viscosity adjustment step ranges from 10 to 70 cP.
3. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The method for preparing the polyethylene polymerization catalyst further comprises a washing step of washing with a second hydrocarbon compound after the recrystallization step.
4. The method for preparing a polyethylene polymerization catalyst according to claim 3, wherein: The method for preparing the polyethylene polymerization catalyst further comprises, after the washing step, a step of preparing a slurry catalyst by adding a second hydrocarbon compound.
5. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The method for preparing the polyethylene polymerization catalyst further adds a second internal electron donor after adding the transition metal compound.
6. The method for preparing a polyethylene polymerization catalyst according to claim 5, wherein: The molar ratio of the magnesium compound to the second internal electron donor is 1:0.01 to 1:
1.
7. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The molar ratio of the magnesium compound to the second hydrocarbon compound is 1:1.5 to 1:
5.
8. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The alcohol is at least one selected from 2-ethylhexanol, methanol, ethanol, propanol, butanol, pentanol, cyclopentanol, hexanol, heptanol, octanol, decanol, dodecanol, 2-methylpentanol, 2-ethylbutanol, cyclohexanol, methylcyclohexanol and methylbenzyl alcohol.
9. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The first hydrocarbon compound is a C9 to C30 hydrocarbon.
10. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The second hydrocarbon compound is a C3 to C8 hydrocarbon.
11. The method for preparing a polyethylene polymerization catalyst according to claim 5, wherein: The first internal electron donor or the second internal electron donor is each independently selected from ethyl benzoate, methyl benzoate, ethyl p-methoxybenzoate, methyl p-ethoxybenzoate, ethyl p-ethoxybenzoate, ethyl p-chlorobenzoate, diisobutyl phthalate, 9,9-bis(methoxymethyl)fluorene, propyl benzoate, isopropyl benzoate, tert-butyl benzoate, tert-butyl 4-(2-aminoethyl)benzoate, ethyl 4-(dimethylamino)benzoate, ethyl 4-(butylamino)benzoate, 4-(bromomethyl)benzoate, tert-butyl 4-(2-aminoethyl)benzoate, tert-butyl 4-(dimethylamino)benzoate, ethyl 4-(butylamino)benzoate, tert-butyl 4-(bromomethyl)benzoate, tert-butyl 4-(2-aminoethyl)benzoate, tert-butyl 4-(2-aminoethyl)benzoate, tert-butyl 4-(dimethylamino)benzoate, tert-butyl 4-(butylamino)benzoate, tert-butyl 4-(bromomethyl)benzoate, tert-butyl 4-(2-aminoethyl ...2-aminoethyl)benzoate, tert-butyl 4-( 4-(2-hydroxyethoxy)benzoic acid methyl ester, 4-(cyanomethyl)benzoic acid methyl ester, 4-(bromomethyl)benzoic acid methyl ester, 3-(bromomethyl)benzoic acid methyl ester, 1,2-dimethoxybenzene, 1,2-diethoxybenzene, 1,2-dibutoxybenzene, 1,2-di-sec-butoxybenzene, 1,2-di-tert-butoxybenzene, tetramethoxybenzene Silane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane, n-propyltriethoxysilane, decyltrimethoxysilane, cyclopentyltrimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethylcyclopentyltrimethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane, tert-butyltriethoxysilane, n-butyltriethoxysilane, isobutyltriethoxysilane, decyltriethoxysilane At least one of trimethoxysilane, triethoxysilane, triethoxysilane, triethoxysilane, triisopropoxysilane, tributyloxysilane, trimethylphenoxysilane, triallyloxysilane, triacetoxysilane, methoxysilane, diisopropyldimethoxysilane, tert-butylmethyldimethoxysilane, dicyclopentyldimethoxysilane, dicyclohexyldimethoxysilane, methyldimethoxysilane, diphenyldimethoxysilane and cyclopentyldimethoxysilane.
12. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The molar ratio of the magnesium compound to the first internal electron donor is 1:0.01 to 1:0.
3.
13. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The molar ratio of the magnesium compound to the transition metal compound is 1:2 to 1:
5.
14. The method for preparing a polyethylene polymerization catalyst according to claim 1, wherein: The recrystallization step is carried out at -7°C to 7°C.
15. A method for preparing polyethylene, comprising the step of polymerizing monomers using the polyethylene polymerization catalyst prepared according to any one of claims 1 to 14.